Model Emotional Brand Experience melalui Integrasi Touchpoint Fisik dan Digital pada Visual Branding Musisi Independen - Rachel Cahya Gunita; Taufik Murtono (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2026)
This study discusses the visual branding design for Gandhi Asta's solo album as an effort to build an independent musician's identity that can compete in the digital music industry while establishing an emotional connection with the audience. The research problem focuses on how an integrated model of physical and digital touchpoints in visual branding can create a brand experience that supports the formation of brand awareness for independent musicians. This study aims to produce a consistent visual identity system through the application of visual elements and interactive media. The method used refers to Alina Wheeler's design stages, which include research, strategy formulation, identity design, supporting media development, and visual asset management. The design results include a logo, illustrations, typography, a color palette, an interactive box set, merchandise, and digital media integrated with barcode-based postcards to connect the audience to exclusive content. Based on survey results, the majority of respondents rated the box set as the most appealing merchandise medium, while design creativity and emotional connection with the audience were identified as crucial factors in following musicians on social media. This design successfully delivers a visual identity capable of strengthening Gandhi Asta's character and increasing brand recognition among independent music audiences.